Beliefs of teachers in training regarding the use of Chilean voseo in the everyday and educational context - Cautín-Epifani, Violeta; Gladic, Jadranka; González, Carolina; Arellano, Rodrigo (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Currently, verbal voseo plays a relevant role within address forms in Chile, which is used in everyday speech, especially in the context of trust, closeness, spontaneous speech and/or informality, as well as as a means to achieve communicative goals. Despite being a widely studied phenomenon, research on its use in educational contexts and in initial teacher training is scarce, so the specific treatment that teachers give to the appearance of voseo forms in school contexts is still unknown. This study explores the beliefs that Spanish language pre-service teachers from 4 Chilean universities have about the use of voseo with samples collected through interviews and questionnaires. The results allowed a characterization of the beliefs participants have about the use of these address forms, either in the educational and/or daily context and their relationship with covert prestige in Chile.
Keywords: Chilean voseo; teaching beliefs; pre-service teachers